Effect of cytoskeleton inhibitors on conidiogenesis and capsule in the long neck yeast Fellomyces examined by scanning electron microscopy - Kopecká, Marie; Ilkovics, Ladislav; Ramíková, Vladimíra; Yamaguchi, Masashi (Chemotherapy, 2010)
BACKGROUND: The aim of this basic study was to investigate by scanning electron microscopy the effects of cytoskeleton inhibitors on conidiogenesis and capsule in the yeast Fellomyces fuzhouensis CBS 8243, related to Cryptococcus neoformans. METHODS: Cells were treated by methyl benzimidazole-2-ylcarbamate (BCM) and latrunculin A (LAT) in yeast extract peptone dextrose medium and examined by scanning electron microscopy. RESULTS: During conidiogenesis, mother cells covered by capsule formed hypha-like stalks and at the hyphal tip yeast-like conidium developed. LAT blocked both stages of conidiogenesis. Inhibited mother cells and conidia became spherical and their capsule disappeared. BCM did not block formation of conidia that were neckless, or affect capsule. Combined application of LAT and BCM blocked both stages of conidiogenesis, cells became spherical and their capsule disappeared. CONCLUSION: Yeast cells with disrupted actin cytoskeleton do not reproduce by conidiogenesis and do not retain inherited cell shape and capsule.
Keywords: bicyklické sloučeniny heterocyklické; Cytoskeleton; tvar buňky; Spores, Fungal; mikroskopie elektronová rastrovací; Thiazolidines; Bridged Bicyclo Compounds, Heterocyclic; spory hub; Basidiomycota; thiazolidiny; Microscopy, Electron, Scanning; cytoskelet; Cell Shape